Tarcza Kształtu Półpłaszczyznyn Wpływem Działania Obciążenia Wewnętrznego - Szelągowski, F. (Engineering Transactions, 1959)
Equations are derived enabling the determination of the stresses Xy, Xx, Yy at any point of a semi-infinite plate acted on by two concentrated internal forces parallel to the edge of the plate. This problem is solved in functions of Schwarz’s formula complex variables using.